Racial Disparities in Civilian Response to Police Use of Force: Evidence From London - Braakmann, Nils (The British journal of criminology, 2025)
This study explores the impact of police use of force on civilian interactions with the police, focussing on neighbourhoods with different ethnic compositions across London. Analysing the effects of three notable police-induced civilian fatalities as well as monthly fluctuations in the Metropolitan Police Service’s use of force, I find a decrease in reported crime and the proportion of crime without a suspect in Black neighbourhoods. These patterns suggest avoidance of police engagement, especially for crimes less likely to be solved. Individual survey data suggests no changes in victimization probabilities for any ethnic group, suggesting that estimates are due to reporting behaviour.